A review of the circumstances and health‐seeking behaviours associated with bat exposures in high‐income countries. (13th June 2022) - Wright, Eryn; Anuradha, Satyamurthy; Richards, Russell; Reid, Simon
Abstract: Human–bat interactions are now the source of the majority of locally acquired human lyssavirus infections in many high‐income countries without hematophagous or 'vampire' bat species. This study aims to identify the most common types and circumstances of bat exposures occurring among members of the general public in high‐income countries with no hematophagous bats, and to describe the health‐seeking behaviours associated with exposures in these settings. We conducted a scoping review of relevant academic and grey literature on bat exposures and confirmed bat lyssavirus infections among members of the general public in Australia, Canada, the United States and high‐income European countries from 1996 to 2019. Case studies and population‐based studies were included for analysis, and findings were extracted and synthesized by the literature type and geographic region. A total of 63 publications were identified, including: 47 case studies and 16 population‐based studies. Overall, most exposures in Australia and Europe were intentionally initiated by humans and involved attempts to handle, touch or help a bat. In North America, however, household exposures were more common and predominantly involved a bat being found in a room or area where a person had slept. Studies also showed that a proportion of bat exposures in high‐income countries go unreported in the absence of a public health investigation and are therefore unlikely to receive prompt treatment. The results of this review suggest that the most effective strategies for preventing bat exposures vary between regions and that health‐seeking behaviours following bat exposures could be improved in high‐income settings.